Evaluation of Antinociceptive Activity of Ficus Religiosa Root Extract in Swiss Albino Mice - Singh, S.; Sangraula, H.; Singh, P. K.; Sarraf, D. P. (Kathmandu University Medical Journal, 2022)
Background Ficus religiosa, commonly known as peepal, is widely distributed in Indian subcontinent. It has been used as an antiepileptic, aphrodisiac, analgesic, anti-inflammatory and laxative in traditional medicine. Objective To explore the analgesic effect of aqueous root extract of Ficus religiosa using thermal and chemical models of pain in swiss albino mice. Method The aqueous aerial root extract of Ficus religiosa was prepared using soxhlet apparatus. The anti-nociceptive effect of the extract at doses of 50 and 100 mg/kg was evaluated using peripheral (acetic acid-induced abdominal writhing), spinal (tail flick) and supra-spinal (hot plate) behavioral models of pain. All data were presented as Mean ± SEM. Statistical differences between Ficus religiosa (50 and 100 mg/kg) and standard control groups were evaluated using Mann-Whitney U test. Result There was significant dose dependent increase in the mean reaction time compared to the vehicle control in hot plate and tail- flick test. In acetic acid induced writhing test, mice treated with Ficus religiosa (50 and 100 mg/kg) exhibited significant dose-dependent decrease in the mean number of writhes (57.45% and 79.20% respectively) compared to the vehicle control. The activity of Ficus religiosa extract at doses of 50 and 100 mg/kg was equipotent to Standard control (Morphine and Indomethacin) used in different test models. Conclusion The extract of Ficus religiosa possesses both central and peripheral analgesic activity thus validating the traditional use of this plant in the management of pain.